Targeting Macroautophagy as a Therapeutic Opportunity to Treat Parkinson’s Disease - Sanchez-Mirasierra, Irene; Ghimire, Saurav; Hernandez-Diaz, Sergio; Soukup, Sandra-Fausia (Frontiers in Cell and Developmental Biology, 2022)
Macroautophagy, an evolutionary conserved catabolic process in the eukaryotic cell, regulates cellular homeostasis and plays a decisive role in self-engulfing proteins, protein aggregates, dysfunctional or damaged organelles and invading pathogens. Growing evidence from in vivo and in vitro models shows that autophagy dysfunction plays decisive role in the pathogenesis of various neurodegenerative diseases, including Parkinson's disease (PD). PD is an incurable and second most common neurodegenerative disease characterised by neurological and motor dysfunction accompanied of non-motor symptoms that can also reduce the life quality of patients. Despite the investment in research, the aetiology of the disease is still unknown and the therapies available are aimed mostly at ameliorating motor symptoms. Hence, therapeutics regulating the autophagy pathway might play an important role controlling the disease progression, reducing neuronal loss and even ameliorating non-motor symptoms. In this review, we highlight potential therapeutic opportunities involved in different targeting options like an initiation of autophagy, Leucine-rich repeat kinase 2 (LRRK2) inhibition, mitophagy, lysosomes, lipid metabolism, immune system, gene expression, biomarkers and also non-pharmacological interventions. Thus, strategies to identify therapeutics targeting the pathways modulating autophagy might hold a future for therapy development against PD.